Intimate partner and nonpartner violence against pregnant women in rural Haiti. - Small, Maria J; Gupta, Jhumka; Frederic, Rikerdy; Joseph, Gabriel; Theodore, Melanie; Kershaw, Trace (International journal of gynaecology and obstetrics: the official organ of the International Federation of Gynaecology and Obstetrics, 2008)
To examine the association between violence experienced by pregnant Haitian women in the previous 6 months and pregnancy-related symptom distress.
Keywords: Adolescent; Adult; Cross-Sectional Studies; Female; Haiti; Humans; Interviews as Topic; Maternal Health Services; Middle Aged; Pregnancy; Pregnancy Complications; Prenatal Care; Spouse Abuse